Dextran sulfate-amplified extracellular matrix deposition promotes osteogenic differentiation of mesenchymal stem cells. (1st March 2022) - Wan, Ho-Ying; Shin, Rita Lih Ying; Chen, Jack Chun Hin; Assunção, Marisa; Wang, Dan; Nilsson, Susie K.; Tuan, Rocky S.; Blocki, Anna
Abstract: The development of bone-like tissues in vitro that exhibit key features similar to those in vivo is needed to produce tissue models for drug screening and the study of bone physiology and disease pathogenesis. Extracellular matrix (ECM) is a predominant component of bone in vivo ; however, as ECM assembly is sub-optimal in vitro, current bone tissue engineering approaches are limited by an imbalance in ECM-to-cell ratio. We amplified the deposition of osteoblastic ECM by supplementing dextran sulfate (DxS) into osteogenically induced cultures of human mesenchymal stem cells (MSCs). DxS, previously implicated to act as a macromolecular crowder, was recently demonstrated to aggregate and co-precipitate major ECM components, including collagen type I, thereby amplifying its deposition. This effect was re-confirmed for MSC cultures undergoing osteogenic induction, where DxS supplementation augmented collagen type I deposition, accompanied by extracellular osteocalcin accumulation. The resulting differentiated osteoblasts exhibited a more mature osteogenic gene expression profile, indicated by a strong upregulation of the intermediate and late osteogenic markers ALP and OCN, respectively. The associated cellular microenvironment was also enriched in bone morphogenetic protein 2 (BMP-2). Interestingly, the resulting decellularized matrices exhibited the strongest osteo-inductive effects on re-seeded MSCs, promoted cell proliferation, osteogenic marker expression and ECM calcification. Taken together, these findings suggest that DxS-mediated enhancement of osteogenic differentiation by MSCs is mediated by the amplified ECM, which is enriched in osteo-inductive factors. We have thus established a simple and reproducible approach to generate ECM-rich bone-like tissue in vitro with sequestration of osteo-inductive factors. Statement of significance: As extracellular matrix (ECM) assembly is significantly retarded in vitro, the imbalance in ECM-to-cell ratio hampers current in vitro bone tissue engineering approaches in their ability to faithfully resemble their in vivo counterpart. We addressed this limitation by leveraging a poly-electrolyte mediated co-assembly and amplified deposition of ECM during osteogenic differentiation of human mesenchymal stem cells (MSCs). The resulting pericelluar space in culture was enriched in organic and inorganic bone ECM components, as well as osteo-inductive factors, which promoted the differentiation of MSCs towards a more mature osteoblastic phenotype. These findings thus demonstrated a simple and reproducible approach to generate ECM-rich bone-like tissue in vitro with a closer recapitulation of the in vivo tissue niche. Graphical abstract: Image, graphical abstract